Induction of Apoptosis through Oxidative Stress Caused by Rubus tereticaulis Leaves Extracts in A549 Cells - ŞEN, ALİ (My University, 2024)
Objective:Plants have been used for medicinal purposes since the beginning of human history and form the basis of modern medicine, and they are also the source of most chemotherapeutic drugs for cancer treatment. This study aims to investigate for the first time the cytotoxic and apoptotic effects of the active ethanol (RTE) and chloroform (RTC) extracts of Rubus tereticaulis leaves in the A549 non-small-cell lung cancer cell line. Materials and Methods:A549 cells were treated with RTE and RTC individually. The MTT assay was used to quantitatively detect RTE and RTC\"s cytotoxic effects. The fluorescent signal indicator H2DCF-DA was used to detect cellular reactive oxygen species (ROS) production. Apoptosis was evaluated by fluorescence microscope after acridine orange/ethidium bromide fluorescent staining, annexin V-FITC and immunoblotting analyses, immunofluorescence, and imaging. Results:Both RTE and RTC induced cytotoxicity in A549 cells in a dose-dependently, which was accompanied with induced ROS accumulation. Both early and late apoptotic cells detected by flow cytometry were increased in the RTE- and RTC-treated cells. In addition, the results show RTC to have higher cytotoxic and apoptotic effects and increased ROS-generation capacity than RTE. Therefore, the polarity of the solvent used to exert the anticancer effect of R. tereticaulis leaves is crucial. Conclusion:This is the first anti-cancer activity study on R. tereticaulis. The results suggest R. tereticaulis leaves to have an anti-cancer effect on lung cancer cells through ROS-mediated apoptosis and RTC to be an effective therapeutic/adjuvant strategy in cancer treatment.
Keywords: Tıp; Histoloji-Embriyoloji; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Histology and Embryology; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Mikrobiyoloji; HÜCRE BİYOLOJİSİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; CELL BIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Moleküler Biyoloji; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Hücre Biyolojisi; Molecular Biology; Biochemistry, Genetics and Molecular Biology (miscellaneous); Cell Biology; Anti-cancer effect; Apoptosis; Lung cancer; Oxidative stress; Rubus tereticaulis